Treatment of coking wastewater by aeration assisted electrochemical oxidation process at controlled and uncontrolled initial pH conditions - Iskurt, Cisel; Keyikoglu, Ramazan; Kobya, Mehmet; Khataee, Alireza (Elsevier, 2020)
The high organic load and toxic content of coking oven wastewater (COW) challenge most of the conventional methods, which focus more on the removal of carbonaceous pollutants and less on the other toxic pollutants such as ammonia. To improve the treatment of COW, which had COD = 6600 mg/L, TOC = 1990 mg/L, SCN-=461 mg/L, NH3-N = 3430 mg/L, phenol = 1452 mg/L, and pH = 9.56, aeration was integrated to the electrochemical oxidation (EO). The effect of initial pH (5-12) and current density (140-700 A/m(2)) on the performance of the process was assessed. Also, the effect of aeration on the treatment of COW was determined by applying as stand-alone and integrated processes (combined and successive steps). All the experiments were performed both at controlled (pH was kept constant) and uncontrolled (pH was not adjusted) conditions. By applying the pseudo-first-order kinetic model, the contribution of aeration to the removal kinetics of the pollutants was clarified. The combined process of aeration/EO achieved 99.8% COD, 92.3% TOC, 100% NH3-N, 100% SCN-, and 100% phenol removal efficiencies. The total cost of the process, including electrical energy and chemical consumption, was determined as 52.10 $/m(3) and 8.60 $/kg COD.
Keywords: Ammonia removal; Boron-doped diamond; Coking wastewater; Electrochemical oxidation; Operation cost